An analysis of the Human Resource Development Climate prevailing in Kerala Agricultural University - Senthilkumar R (Department of Extension, College of Veterinary and Animal Sciences, 1999)
The HRD climate prevailing in the Kerala Agricultural University and as perceived by its scientists was studied. In all, 262 scientists from main, regional and remote stations constituted the sample. The HRD climate studied was in terms of 12 major constituent dimensions, viz., management philosophy, training, career planning and development, manpower planning and forecasting, performance appraisal communication, team work, transfer, promotion, rewards and organizational culture. It was seen that organizational culture had been identified as the relatively most dominant dimension of HRD climate followed in that order by teamwork, transfer, management philosophy, communication, career planning and development, placement, rewards, performance appraisal, promotion, training, and manpower planning and forecasting. Manpower planning and forecasting being the weakest dimension need immediate intervention. Besides looking into the strength of various dimensions and components the issue of HRD climate was examined from the angle of the number of scientists perceiving it as favourable, moderately favourable and unfavourable. Considering only the percentage of scientists who perceived the various dimensions to be favourable, the latter were ordered. Accordingly, it was seen that comparatively the highest percentage of scientists perceived the dimension transfer to be favourable followed in that order by teamwork, placement, communication, organizational culture, career planning and development, rewards, manpower planning and forecasting, management philosophy, training, promotion and performance appraisal. Since the percentage of scientists perceiving the HRD dimension, performance appraisal to be favourable was the least, immediate reformative measures are warranted.